2023
DOI: 10.1038/s41586-023-06063-y
|View full text |Cite
|
Sign up to set email alerts
|

Personalized RNA neoantigen vaccines stimulate T cells in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is lethal in 88% of patients1, yet harbours mutation-derived T cell neoantigens that are suitable for vaccines 2,3. Here in a phase I trial of adjuvant autogene cevumeran, an individualized neoantigen vaccine based on uridine mRNA–lipoplex nanoparticles, we synthesized mRNA neoantigen vaccines in real time from surgically resected PDAC tumours. After surgery, we sequentially administered atezolizumab (an anti-PD-L1 immunotherapy), autogene cevumeran (a maximum of 20 neoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
218
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(221 citation statements)
references
References 63 publications
3
218
0
Order By: Relevance
“…Despite these challenges, impressive progress has been made in the research and development of mRNA therapeutics and vaccines. Most recently, Luis A. Rojas et al have reported the promising result of a Phase 1 clinical trial in which personalized uridine mRNA neoantigen vaccines induced substantial T cell activity in postsurgery patients with pancreatic ductal adenocarcinoma . The remarkable success of the mRNA vaccines for COVID-19, along with recent expansion of this technology into treatment of most lethal cancers, has validated the great promise of this new class of medications and significantly enhanced the chance to witness their extensive applications in the near future.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…Despite these challenges, impressive progress has been made in the research and development of mRNA therapeutics and vaccines. Most recently, Luis A. Rojas et al have reported the promising result of a Phase 1 clinical trial in which personalized uridine mRNA neoantigen vaccines induced substantial T cell activity in postsurgery patients with pancreatic ductal adenocarcinoma . The remarkable success of the mRNA vaccines for COVID-19, along with recent expansion of this technology into treatment of most lethal cancers, has validated the great promise of this new class of medications and significantly enhanced the chance to witness their extensive applications in the near future.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…The key next step is determining the optimal vaccine modality to elicit highly functional and de novo CD8 + T cell responses, particularly in cure settings given concerns regarding the irreversible dysfunctional features of preexisting responses [21 ▪▪ ]. A number of recent studies using neoantigen epitope-based vaccines in novel formats, such as mRNA [89,90] and heterologous simian adenovirus/self-amplifying RNA immunization [91] provide reason for optimism. Inducing tissue-resident HIV-specific CD8 + T cell memory responses at relevant mucosal sites will also be another important part of future vaccine efforts [92].…”
Section: Implications For Hiv T Cell Vaccine Developmentmentioning
confidence: 99%
“…Rojas and colleagues recently trialled the cevumeran neoantigen mRNA vaccine in combination with modified FOLFIRINOX and anti‐PD‐L1 antibody (atezolizumab) in resected PDAC patients [86]. In 50% of patients, a large neoantigen‐specific T‐cell population was observed [86]. The median recurrence‐free survival of those patients with vaccine‐expanded T‐cells (referred to as the responders) was significantly longer than in patients lacking those T‐cells (called the non‐responders) [86].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested the vaccine may therefore be more effective in early-stage tumours [85]. Finally, personalised neoantigen mRNA vaccines are gradually being trialled in PDAC patients [86]. Rojas and colleagues recently trialled the cevumeran neoantigen mRNA vaccine in combination with modified FOLFIRINOX and anti-PD-L1 antibody (atezolizumab) in resected PDAC patients [86].…”
mentioning
confidence: 99%
See 1 more Smart Citation